The Problem of Symbolic Interaction and of Constructing Self - Konecki, Krzysztof T. (Qualitative Sociology Review, 2005)
In the article we make an analysis of a thesis that verbal symbolic interaction is a necessary condition of constructing self. The main concepts used in the paper are: symbolic interaction, self and corporality. The aforementioned thesis and the concept of symbolic interaction originate from G.H Mead, who set the trend of thinking about interaction in human society in sociology and social psychology. This influence is noticeable up to this day. Symbolic interaction as a tool of understanding others actions and informing partners about our intensions is clearly visible in “languagecentred” and anthropocentrically oriented analyses of interactions as well as in the concentration on linguistic conditions of creating a self. Self is understood as an interpreted concept of a person but mainly in a process of social perception of a human by others occurring in interactions based on verbal language. In the article we want to develop a thesis about “nonlinguistic” possibilities of constructing interactions and self. The aforementioned thesis has been many times elaborated so far together with critical analyses of G. H. Mead (Irvin, 2004, Sanders, 1993, 1999, 2003; Myers, 1999, 2003). We want to integrate these elaborations, including our empirical experiences from a research on “The Social World of Pet’s Owners’ (research done in 2001-2005) on theoretical level and concentrate more on corporality and emotions issues and their relations to symbolic interaction and self. G.H. Mead’s views on this topic are analysed with regard to their methodological consistency and adequacy. In the article there is another thesis proposed, that interactions between animals also have meanings and, sometimes, symbolic nature, or sometimes, non symbolic one, and not necessarily related to use of a verbal language. The creation of self is connected with issues of corporality that includes: 1. nonverbal communication, 2. a relation of bodies in physical space, 3. the so called “kinesthetic empathy”, 4. emotions connected with body, mind and self processes. These elements of corporality may be the basis for taking the role of other. Researches and analyses of many sociologists (beginning from Ch. H. Cooley) show that self is often pre-verbal and that exclusion of an individual from her/his surroundings takes place also with the aid of the body and emotions tightly connected with functioning of self. The analysis of interactions between humans and animals provides us with much methodological and theoretical inspiration. Those researches and analyses obviously face a problem of “anthropomorphization of human behaviour”, which is of frequent occurrence both among researchers and ordinary people. New sociological sub-discipline called the sociology of human - non-human animals relationships adds a lot of new threads to the abovementioned deliberations on conditions of constructing self.